PENGEMBANGAN MULTIMEDIA INTERAKTIF ‘JELAJAH BUDAYA BERSAMA RAJO’ BERBASIS ARTICULATE STORYLINE 3 PADA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SD - Zuardi; Amanda Berlia Bersky (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education in the 5.0 digital era requires innovative and interactive learning in line with the demands of the 21st century. To realise this, interactive IT-based media centred on students is needed. However, in elementary schools, the use of interactive media is still limited to simple videos or digital quizzes. However, professional software like Articulate Storyline 3 is capable of integrating video, audio, and images to create more engaging and meaningful learning experiences. This research aims to develop interactive multimedia